2015
DOI: 10.1016/j.aca.2015.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in carbon nanomaterial-based electrochemical sensors for biomolecules: A review

Abstract: Carbon nanomaterials are advantageous for electrochemical sensors because they increase the electroactive surface area, enhance electron transfer, and promote adsorption of molecules. Carbon nanotubes (CNTs) have been incorporated into electrochemical sensors for biomolecules and strategies have included the traditional dip coating and drop casting methods, direct growth of CNTs on electrodes and the use of CNT fibers and yarns made exclusively of CNTs. Recent research has also focused on utilizing many new ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
267
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 494 publications
(270 citation statements)
references
References 157 publications
1
267
0
2
Order By: Relevance
“…BSA solutions were prepared in phosphate-buffered saline, PBS (pH 7.2). Kinetic studies were conducted with BSA solutions (1 mg/mL) at varying adsorption times (5,10,20,30, 60 and 90 min) at room temperature while shaking at 150 rpm. Prior to BSA adsorption, expanded graphite (~100 mg) was equilibrated overnight in PBS (2.0 mL) to prevent adsorption of environmental contaminants from the air and then the excessive liquid phase was separated by centrifugation.…”
Section: Adsorption Of Bovine Serum Albumin (Bsa)mentioning
confidence: 99%
See 1 more Smart Citation
“…BSA solutions were prepared in phosphate-buffered saline, PBS (pH 7.2). Kinetic studies were conducted with BSA solutions (1 mg/mL) at varying adsorption times (5,10,20,30, 60 and 90 min) at room temperature while shaking at 150 rpm. Prior to BSA adsorption, expanded graphite (~100 mg) was equilibrated overnight in PBS (2.0 mL) to prevent adsorption of environmental contaminants from the air and then the excessive liquid phase was separated by centrifugation.…”
Section: Adsorption Of Bovine Serum Albumin (Bsa)mentioning
confidence: 99%
“…Development of novel nanostructured carbons and methods for their surface modification expanded the choice of materials and led to the applications in biosensors, coatings for medical devices, drug and gene delivery carriers and bioimaging [3]. Current interest to biomedical applications of novel nanostructured carbon materials is based on their structural, mechanical, physical and chemical properties, which are often superior to other materials [4,5]. This interest is supported by the fact that many carbon materials have good biocompatibility and can be used in direct contact with blood and human tissues [6].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that ferric hydroxide-Nafion film-coated carboxylic acid-modified carbon nanotubes changed dopamine in drosophila [40]. Functionalization of carbon nanotubes with poly (diallyl dimethylammonium chloride) (PDDA) reduced the detection limit of dopamine [41] .…”
Section: Advances In the Therapeutic Effects Of Carbon Nanotubes On Mmentioning
confidence: 99%
“…Functionalized CNT electrodes have been used for neurotransmitter detection with high sensitivity and selectivity. Vertically aligned CNTs can lead to more reproducible surfaces with CNT ends exposed to enhance sensitivity [84]. CNT yarns are made of multiple CNT fibres twisted together and these have been utilized by Yang and team for production of CNT yarn microelectrodes (CNTYMEs).…”
Section: Carbon Nanotubes As Electrochemical Biosensors In Neurosciencementioning
confidence: 99%